THE DIGITAL ERA IN INFLUENCE ON WOMEN'S CONSUMER BEHAVIOR IN THE BUSINESSWOMAN BOND COMMUNITY INDONESIA (IWAPI) NORTH SUMATRA - Aisyah, Nur; Suryani, Wan; Meutia, Riza Fanny (Yayasan Education and Social Center, 2024)
This study aims to determine the influence of the digital era on women's consumer behavior in the Indonesian Businesswomen Association (IWAPI) in the North Sumatra community. Understanding consumer behavior in the digital age is an essential and critical strategy for achieving a competitive advantage. Consumer or individual behavior provides a challenge for the Indonesian Businesswomen's Association community, which requires providing an understanding of digitalization both in e-commerce and the need to provide marketing that uses electronic devices or the Internet and provides opportunities for consumers to seek Information about products to be sold or purchased, as well as obtain testimonials from other consumers about their experiences after buying or consuming a product. The purpose of this study is to present a systematic literature review on the effect of digitalization on consumer behavior. The analysis used in this research is qualitative, with the analysis used in this research being thematic analysis with analytical techniques to identify patterns from data related to perceptions. The results of this study show that digitalization causes a migration of consumer behavior from offline (physical dimension) to online (digital dimension). IWAPI must adapt to changes in consumer behavior, which is one of the keys to success in maintaining the survival of every entrepreneur